Burning bright or burning out: a qualitative investigation of leader vitality - Shapiro, Jamie (Frontiers in Psychology, 2023)
Leaders of organizations have incessant demands placed on them, including cultivating teams, building culture, and increasing the bottom line, in addition to caring for followers' wellbeing and thriving. Numerous resources are required to meet these continuous demands, and vitality is one of the most valuable. Through interviewing 20 of the most influential and pressured leaders of Fortune 1000 companies, this qualitative study answers three important questions: what drains vitality, what fosters it, and how do leaders most effectively utilize vitality for followers? The results shed light on psychological mechanisms that drain leaders' vitality, including emotional labor, self-control, loss of job control, the unproductive mindsets of others, and isolation created from the role. In terms of fostering vitality, several of the pathways of the PERMA+4 model of well-being were highlighted, including fostering relationships, physical health, accomplishment, mindset, meaning, environment, and engagement. Two additional themes that foster vitality included job autonomy and time away from work. Themes emerged that underscore how leaders utilize their vitality for followers, and the potentially detrimental impacts to leadership when leaders are drained. Overall, results highlight the importance of vitality and self-care as critical for leaders' ability to maximize their leadership performance.